Artesunate attenuates inflammatory injury and inhibits the NF-κB pathway in a mouse model of cerebral ischemia. Issue 11 (November 2021) - Liu, Ying; Dang, Wei; Zhang, Shiyang; Wang, Lina; Zhang, Xiangjian
Objective: Inflammation is an important factor in the pathological process of cerebral ischemia. Artesunate exhibits a broad range of anti-inflammatory properties in many diseases. We investigated the potential protective effect of artesunate against cerebral ischemia and the related mechanisms. Methods: Mice were divided into distal middle cerebral artery occlusion (dMCAO), sham, low dose, and high dose groups and subjected to dMCAO, except for the sham group. The low and high dose groups were administered artesunate (15 and 30 mg/kg), and the neuroprotective effects were analyzed by evaluating infarct volumes and neurological deficits. Microglial activation and neutrophil infiltration were evaluated by immunofluorescence, immunohistochemical staining, and western blotting. Inflammatory mediators were measured by enzyme-linked immunosorbent assays. Nuclear factor (NF)-κB nuclear translocation was detected by immunofluorescence and western blotting. Results: Compared with the dMCAO group, artesunate significantly improved neurological deficit scores and infarct volumes and ameliorated inflammation by reducing neutrophil infiltration, suppressing microglial activation, and downregulating tumor necrosis factor-α and interleukin-1β expression. Furthermore, artesunate inhibited nuclear translocation of NF-κB and inhibitor protein α proteolysis. Conclusions: Artesunate protected against inflammatory injury by reducing neutrophil infiltration and microglial activation, suppressing inflammatory cytokines, and inhibiting the NF-κB pathway. Therefore, artesunate is a potential ischemic stroke treatment.